THE THERAPIST-PATIENT RELATIONSHIP IN THE CONTEMPORARY WORLD - Ospina Muñoz, Doris Elena (Investigación y Educación en Enfermería, 2008)
Objective: to meditate on the epistemology’s challenges of the therapist-patient relationship in the contemporary world. This article arises the bibliographical revision in order to participate in the public merits convocation, in Nursing School, University of Antioquia, 2004. Conclusions: Today’s therapist is heading to negotiate with multiple powers, derived of the cultural knowledge, the application of the technology, the access to the information and market relationships that mediate in the benefit of the health services to complete their caregiver or caretaker function. For that reason, more than a healer-caretaker today’s therapist is advisor or mediator between patient and the systems health. This mediation ia enclose by ethical conflicts that demand to be approached in extensive during the health professional teaching process.